Infections in patients with rheumatoid arthritis receiving tofacitinib versus tumour necrosis factor inhibitors: results from the open-label, randomised controlled ORAL Surveillance trial - Balanescu, Andra-Rodica; Citera, Gustavo; Pascual-Ramos, Virginia; Bhatt, Deepak L; Connell, Carol A; Gold, David; Chen, All-Shine; Sawyerr, Gosford; Shapiro, Andrea B; Pope, Janet E; Schulze-Koops, Hendrik (Annals of the rheumatic diseases, 2022)
ObjectivesTo characterise infections in patients with rheumatoid arthritis (RA) in ORAL Surveillance.MethodsIn this open-label, randomised controlled trial, patients with RA aged≥50 years with ≥1 additional cardiovascular risk factor received tofacitinib 5 or 10 mg two times per day or a tumour necrosis factor inhibitor (TNFi). Incidence rates (IRs; patients with first events/100 patient-years) and hazard ratios (HRs) were calculated for infections, overall and by age (50–<65 years; ≥65 years). Probabilities of infections were obtained (Kaplan-Meier estimates). Cox modelling identified infection risk factors.ResultsIRs/HRs for all infections, serious infection events (SIEs) and non-serious infections (NSIs) were higher with tofacitinib (10>5 mg two times per day) versus TNFi. For SIEs, HR (95% CI) for tofacitinib 5 and 10 mg two times per day versus TNFi, respectively, were 1.17 (0.92 to 1.50) and 1.48 (1.17 to 1.87). Increased IRs/HRs for all infections and SIEs with tofacitinib 10 mg two times per day versus TNFi were more pronounced in patients aged≥65 vs 50–<65 years. SIE probability increased from month 18 and before month 6 with tofacitinib 5 and 10 mg two times per day versus TNFi, respectively. NSI probability increased before month 6 with both tofacitinib doses versus TNFi. Across treatments, the most predictive risk factors for SIEs were increasing age, baseline opioid use, history of chronic lung disease and time-dependent oral corticosteroid use, and, for NSIs, female sex, history of chronic lung disease/infections, past smoking and time-dependent Disease Activity Score in 28 joints, C-reactive protein.ConclusionsInfections were higher with tofacitinib versus TNFi. Findings may inform future treatment decisions.Trial registration number NCT02092467.